2013
DOI: 10.1088/1748-9326/8/2/024036
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological performance of extensive green roofs in New York City: observations and multi-year modeling of three full-scale systems

Abstract: Green roofs can be an attractive strategy for adding perviousness in dense urban environments where rooftops are a high fraction of the impervious land area. As a result, green roofs are being increasingly implemented as part of urban stormwater management plans in cities around the world. In this study, three full-scale green roofs in New York City (NYC) were monitored, representing the three extensive green roof types most commonly constructed:(1) a vegetated mat system installed on a Columbia University res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
123
1
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(149 citation statements)
references
References 33 publications
14
123
1
3
Order By: Relevance
“…This is confirmed by several studies showing that the fraction of water retained decreases as the event sum precipitation increases [21,26,27] and that retention increases as substrate initial moisture decreases [28]. Significant improvements in detention performance are also found at lower initial substrate moistures [29], mainly due to the effect of initial losses by retention, but possibly also affected by the fact that hydraulic conductivity increases as soil moisture content increases.…”
Section: Climatesupporting
confidence: 70%
See 3 more Smart Citations
“…This is confirmed by several studies showing that the fraction of water retained decreases as the event sum precipitation increases [21,26,27] and that retention increases as substrate initial moisture decreases [28]. Significant improvements in detention performance are also found at lower initial substrate moistures [29], mainly due to the effect of initial losses by retention, but possibly also affected by the fact that hydraulic conductivity increases as soil moisture content increases.…”
Section: Climatesupporting
confidence: 70%
“…There is a large inter-event variability shown in most reported studies with reported retention from 0 to 100%, showing a decrease in retention with increasing event sum precipitation [9,21,26,27], but also, other factors such as antecedent soil moisture content are found to be important.…”
Section: Retention Performancementioning
confidence: 93%
See 2 more Smart Citations
“…Volume reduction decreases as precipitation depth increases (Figure 4a). Runoff was stated to follow a second order polynomial equation in several studies [19][20][21]. This relationship works well for describing slow underflow drainage generated by relatively light precipitation, but would not apply for heavy precipitation or with a water storage reservoir installed.…”
Section: Hydrologic Performance Curvesmentioning
confidence: 99%